ANTISIPASI RESTITUSI PAJAK PERTAMBAHAN NILAI ATAS KEGIATAN EKSPOR DAN IMPOR PADA PT YKK ZIPCO INDONESIA - Munawaroh, SE., AK., MM., CA. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
The purpose of this research is to decide the strategy in anticipating and reducing the restitution of Value Added Tax (VAT) to PT YKK Zipco Indonesia, a foreign capital company conducting export and import activities. The research method used is descriptive to describe the calculation of VAT and VAT restitution mechanism conducted by PT YKK Zipco Indonesia based on the prevailing rules, and strategy in anticipating VAT restitution by utilizing Bonded Zone facility. This research analyzes the positive impact of tax planning in anticipating VAT restitution